Sex modifies the association between malnutrition and chronic kidney disease in community-dwelling older adults in the United States - Rongting Zhang; Ke Zhu; Kaijun Zhang; Yinxia Zhu; Yani Wang; Ying Liao; Yong Fang; Yunli Shen (BMC Geriatrics)
Abstract Background Previous studies focused on the relationship between nutritional status and adverse outcomes in patients with chronic kidney disease (CKD). However, the relationship between malnutrition and CKD in community-dwelling older adults in the United States is largely unknown. Methods Overall, 8,219 participants were included in this study, and classified as normal nutritional status, mild malnutrition, and moderate to severe malnutrition by Controlling Nutritional Status (CONUT) score. The relationship between malnutrition and the risk of CKD was investigated through a multivariable logistic regression analysis. Results The average age of participants in this study was 73.0 ± 5.5 years, 3,517 (40%) had CKD. A multivariate logistic regression model revealed that, compared to a normal nutritional state, malnutrition was significantly associated with an increased risk for CKD. The adjusted odds ratios (OR) for mild and moderate to severe malnutrition were 1.27 (95% confidence interval [CI]: 1.04–1.54) and 1.88 (95% CI: 1.19–2.97), respectively. However, among male participants, malnutrition did not show a relationship with the prevalence of CKD, with adjusted ORs of 1.00 (95% CI: 0.78–1.30) for mild malnutrition and 1.47 (95% CI: 0.87–2.49) for moderate to severe malnutrition. Our findings showed that there was an interaction between sex and malnutrition in relation to CKD risk (P for interaction < 0.001). Conclusions In elderly participants, malnutrition is significantly correlated with a higher prevalence of CKD, and sex can modify the relationship between them.